1999
DOI: 10.1016/s0022-5347(05)68936-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Outcome After Radical Cystectomy for Bladder Cancer: A Retrospective Study of a Homogeneous Patient Cohort

Abstract: Tumor stage and nodal involvement are the only independent predictors of survival to be used to select the optimal therapy after radical cystectomy, stratify patients in controlled trials and evaluate new prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
138
1
12

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(164 citation statements)
references
References 33 publications
10
138
1
12
Order By: Relevance
“…Response rates are comparable to those reported in previous chemoradiotherapy series, including the one randomised comparison with radiotherapy. The outcomes for large locally advanced bladder tumours with extravesical extension are poor regardless of the treatment modality used (Bassi et al, 1999;Gschwend et al, 2002). A majority of patients with complete pathological response retain their bladders free from invasive relapse, while about one-quarter will develop superficial recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Response rates are comparable to those reported in previous chemoradiotherapy series, including the one randomised comparison with radiotherapy. The outcomes for large locally advanced bladder tumours with extravesical extension are poor regardless of the treatment modality used (Bassi et al, 1999;Gschwend et al, 2002). A majority of patients with complete pathological response retain their bladders free from invasive relapse, while about one-quarter will develop superficial recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Several studies have evaluated the clinical and pathological prognostic factors after cystectomy for muscle-invasive UC. Advanced pathologic stage, nodal involvement, tumour size greater than 3 cm, elevated creatinine and lymphovascular invasion are independent risk factors for recurrence, [12][13][14][15] while advanced pathologic stage and nodal involvement are independent prognostic factors for survival. 14,16 A nomogram predicting recurrence risk after radical cystectomy for bladder cancer was recently developed to improve the predictability of accurate risk assessment in patients after this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced pathologic stage, nodal involvement, tumour size greater than 3 cm, elevated creatinine and lymphovascular invasion are independent risk factors for recurrence, [12][13][14][15] while advanced pathologic stage and nodal involvement are independent prognostic factors for survival. 14,16 A nomogram predicting recurrence risk after radical cystectomy for bladder cancer was recently developed to improve the predictability of accurate risk assessment in patients after this procedure. 17 While these traditional prognostic factors provided useful estimates for recurrence risk and survival, significant variations within each prognostic group based on the heterogeneity of tumour biology were observed Similarly, patients with locally advanced (T4b and N2-3) or metastatic disease (M1) at diagnosis or during follow-up demonstrate variable response rates to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic significance of the presence of lymphovascular invasion (LVI) on transurethral resection of bladder tumour (TURBT) and radical cystectomy (RC) specimens is still controversial, with some studies showing an independent prognostic effect [2][3][4][5][6] and others showing no effect [7][8][9][10]. Other studies have shown a correlation of LVI with shorter survival that is not independent of pathological stage [11]. In addition, LVI at TURBT has been shown to be associated with understaging and worsened disease-specific survival (DSS) after RC [12].…”
Section: Introductionmentioning
confidence: 99%